Tumor Mimicking in Musculoskeletal System in Surabaya: A Case Series - Bayu Antara Hadi; Mouli Edward (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2020)
ABSTRACTMusculoskeletal tumors are potential causes of heavy morbidity and economic burdens for patients. There are often cases suspected as musculoskeletal tumors based on a specific diagnostic modality because of overlapping features upon physical examination or a tumor-like appearance from the radiological examination, the more reason for triple diagnosis to be performed for an exact diagnosis.  We report 5 cases of fractures tumor-mimicking lesions. The First patient, a patient with MRI revealing a primary malignant bone tumor, but with plain thorax x-ray and FNAB, the diagnosis was tuberculosis arthritis of the elbow. The second patient shows metastatic proses with plain radiographic, but from open biopsy, the diagnoses fall to chronic osteomyelitis. The third patient had a history of papillary carcinoma thyroid with pathological fracture of proximal of the left femur, but the biopsy shows a hypercalcemic state. The fourth patient, had mass size 20x15 cm at the thigh, but the biopsy shows Non-Specific Chronic Osteomyelitis. The fifth patient with progressive swelling of the left knee for one year, 10x10 cm in size, the biopsy showed no sign of malignancy but tuberculosis of left distal femur. In conclusion, standard comprehensive diagnosis steps consisting of clinical history, imaging, laboratory and histopathological examinations are crucial to differentiate tumor-mimicking lesions from neoplasms, thus ensuring proper treatment.Keywords: Tumour mimicking, osteosarcoma, chondroma, malignancy